Peripheral neuropathy : when the numbness, weakness, and pain won't stop - Latov, Norman (AAN Press quality of life guide., 2007)
This indispensable guide will help millions of people understand Peripheral Neuropathy, so that they can take control of their lives and make informed decisions. In addition, it will be a useful resource for their families, caregivers, and health care providers.